Radiofrequency ablation for spinal osteoid osteoma: A systematic review of safety and treatment outcomes. (May 2022) - Sagoo, Navraj S.; Haider, Ali S.; Chen, Andrew L.; Vannabouathong, Christopher; Larsen, Kylan; Sharma, Ruhi; Palmisciano, Paolo; Alamer, Othman Bin; Igbinigie, Matthew; Wells, Daniel B.; Aoun, Salah G.; Passias, Peter G.; et al.
Abstract: Aim: We sought to systematically assess and summarize the available literature on the clinical outcomes and complications following radiofrequency ablation (RFA) for painful spinal osteoid osteoma (OO). Methods: PubMed, Scopus, and CENTRAL databases were searched in accordance with PRISMA guidelines. Studies with available data on safety and clinical outcomes following RFA for spinal OO were included. Results: In the 14 included studies (11 retrospective; 3 prospective), 354 patients underwent RFA for spinal OO. The mean ages ranged from 16.4 to 28 years (Females = 31.3%). Lesion diameters ranged between 3 and 20 mm and were frequently seen in the posterior elements in 211/331 (64%) patients. The mean distance between OO lesions and neural elements ranged between 1.7 and 7.4 mm. The estimated pain reduction on the numerical rating scale was 6.85/10 (95% confidence intervals [95%CI] 4.67–9.04) at a 12–24-month follow-up; and 7.29/10 (95% CI 6.67–7.91) at a >24-month follow-up (range 24–55 months). Protective measures (e.g., epidural air insufflation or neuroprotective sterile water infusion) were used in 43/354 (12.1%) patients. Local tumor progression was seen in 23/354 (6.5%) patients who were then successfully re-treated with RFA or open surgical resection. Grade I-II complications such as temporary limb paresthesia and wound dehiscence were reported in 4/354 (1.1%) patients. No Grade III-V complications were reported. Conclusion: RFA demonstrated safety and clinical efficacy in most patients harboring painful spinal OO lesions. However, further prospective studies evaluating these outcomes are warranted. Highlights: Radiofrequency ablation (RFA) may be a viable therapy for painful spinal osteoid osteoma (OO). Pain scores significantly improved at 12-24-month and >24-month follow-ups. Local control (LC) rates ranged between 87.5% and 100% at varying follow-ups (1–6 years). Overall, Grade I-II complications were reported in 4/354 (1.1%) patients.